Liberalism under siege : the political thought of the French doctrinaires - Crăiuțu, Aurelian (Applications of political theory., 2003)
Liberalism Under Siege: The Political Thought of the French Doctrinaires is a compelling examination of the French Doctrinaires, a largely neglected group of liberal thinkers in post-revolutionary France who were proponents of a nuanced sociological and historical approach to democracy. It combines textual analysis and historical interpretation to explore the Doctrinaires' ideas on the French Revolution, democracy, political power, sovereignty of reason, publicity, capacity, and representative government.